Systematic Review: Performance Indicators And Their Role In Hospitals - Influence On Patient Outcomes And Satisfaction (The Review of Diabetic Studies, 2025)
Background: Cultural competence in healthcare delivery is essential for addressing health disparities and improving patient outcomes in increasingly diverse populations. This systematic review examines cultural competence indicators and assessment tools used in healthcare settings and their relationship with patient outcomes.Methods: Following PRISMA guidelines, we conducted a systematic search of electronic databases for studies published between 2000 and 2024 that described cultural competence assessment tools or examined associations between cultural competence indicators and patient outcomes.Results: The review identified 47 distinct cultural competence assessment tools across individual provider, organizational, and patient-reported levels. Seven common domains of cultural competence measurement were identified, with varying prevalence and association with patient outcomes. Language Access Services and Cross-Cultural Communication Skills demonstrated the strongest associations with patient outcomes.Conclusion: This review provides a comprehensive synthesis of cultural competence measurement in healthcare and highlights the importance of communication-focused aspects of cultural competence for improving patient outcomes. Recommendations for research and practice are provided.